STRATEGI PENGENDALIAN KONFLIK - Hamengkubuwono, Hamengkubuwono; Kristianto, Martinus Novi; Kristiawan, Muhammad (Graduate Program Magister Manajemen Pendidikan, 2020)
This study found out how to control organizational conflict and its influence on the work motivation of employees of CV. Surya Satwa Banyuasin Group. The research method used is a qualitative method, because the problems in this study are described in narrative form. Data collection techniques in this study were observation and interviews with the leadership and one employee of CV. Surya Satwa Banyuasin Group as a guest speaker representing 30 employees. Through this research, the results obtained that with an effective organizational conflict control strategy in the form of compromise, unity, coercion, collaborative and competition will affect the increase in employee motivation, otherwise if it does not implement an effective organizational conflict control strategy, it will affect the decrease in employee motivation. Thus, it can be concluded that organizational conflicts managed by using appropriate conflict control strategies can reduce the bad influence on employee work motivation. Because if employees have good work motivation, their performance and productivity will also increase.